Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1538115246 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 1538115246 records from 26493 constituent datasets: 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 ?m. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 9 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 22 records from Ahuyentamiento, rescate y reubicaci?n de fauna en el ?rea de influencia directa del proyecto Hidroel?ctrico Mulatos II. 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 6652 records from Inventory of plant species through Benin (West Africa). 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 505 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 4109 records from South Caribbean Diversity. 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 1127 records from marine sediment metagenome Metagenome. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 873 records from Programme ACT : R?partition Grive musicienne 2006 - 2010 Coordonn?es GPS Lambert 93. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1968 records from Estudio flor?stico de los bosques mes?filos de la Sierra Mazateca de Oaxaca, M?xico. 371 records from Bannwald Burghauser Forst. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 948 records from Bulletin du Mus?um d'Histoire Naturelle [1895- ]. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 290 records from Donn?es 2016 P?lobate brun Comit? D?partemental de Protection de la Nature et de l'Environnement. 54 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 1741 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2127 records from ZUEC-OPH - Cole??o de Ophiuroidea do Museu de Zoologia da UNICAMP. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 276 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 20520 records from University of Guam Insect Collection. 1569 records from Pollen record of sediment core Bokanjacko Blato 1. 391 records from Planktic foraminifera abundance of Hole 32-310. 19 records from Dinoflagellate abundance of Hole 81-554. 174 records from Artenvielfalt des "Gr?nen Klassenzimmers". 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 102 records from Nannofossil abundance of Hole 24-232. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 1189 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 4083 records from MCP-Aves - Cole??o de Aves. 135 records from Nannofossil abundance of Hole 36-329. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 100 records from Nematode genera abundances at the Arctic H?kon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 147 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 ?m. 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 ?m. 14 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 778 records from Bird specimens of Saitama Museum of Natural History. 371 records from orthopteracollections-nhmj-ioj. 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 10788 records from Collections of Bioclass, school #179, Moscow. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14576 records from Inventario de flora, avifauna, mam?feros, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedici?n cient?fica en la ventana Mesay en el sector sur del Parque Nacional Natural Serran?a de Chiribiquete. 1967 records from Fototrampeo de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 4 records from Dinoflagellate abundance of Hole 14-144. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 38865 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 277417 records from Digitalizaci?n y sistematizaci?n de las colecciones biol?gicas del INECOL (Herbario). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 477 records from Planktic foraminifera distribution of sediment core SU81-07. 231 records from Range table from benthic foraminifers in ODP Hole 161-974B. 926 records from Determinaci?n del estado actual de cinco especies de cact?ceas amenazadas del estado de Tamaulipas, M?xico. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 ?m). 1156 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 382 records from Collection Echinodermata - ZMB. 434 records from Inventario herpetofaun?stico del noroeste de Hidalgo. 32640 records from EDP Foz-Tua: Macrophytes ? Ecological Monitoring Program [2011-2015]. 244 records from WildesMoor bei Schwabstedt. 677 records from The Paleontological Collections at the Bayerische Staatssammlung f?r Pal?ontologie und Geologie. 379 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 32 records from Antarctic Pycnogonids II. 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 7 records from Description of lithologic section units of IODP Hole 325-M0052A. 10 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 212 records from Donn?es des naturalistes POHIER et LEFORT provenant de la base de donn?e du SINP ?le-de-France CETTIA. 2560 records from Upper Silesian Museum, Bird Observations. 268 records from Bri?fitos del cerro Tacarcuna-Choc?, en el marco del proyecto Colombia BIO 2017. 190 records from CNMA/Colecci?n de Mam?feros de la Estaci?n de Biolog?a Chamela. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 847 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 98 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 269 records from SEWBReC Springtails and allies (South East Wales). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 4 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 2189 records from Jard?n Bot?nico Atl?ntico, Gij?n: JBAG. 36 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 158115 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgel?nde. 3647 records from Donn?es rhopaloc?res collect?es par le CEN Aquitaine entre 1970 et 2015. 349 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Donn?es sur les Opisthobranches et Planaires de Mayotte. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 419 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 129 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 69 records from BIRDRACE Pfeifenten. 1389 records from Phytoplankton abundance in surface water during cruise CD61. 5335 records from Marine metagenome ICM_JRV. 29 records from Total foraminifera counts of trap L3_92_45. 146 records from Donn?es de la naturaliste Laurence Beauchamp. 52 records from Collections ichtyologiques et herp?tologiques (BOUM). 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 751 records from Programme ACT : R?partition Pie bavarde 2007 - 2011 Coordonn?es GPS Lambert 93. 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colecci?n de mariposas del Museo de Entomolog?a de la Universidad del Valle. 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 191 records from sediment microorganism Metagenome. 6192 records from NE Scotland fish records 1800-2010. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Cear? State) and Sete Cidades (Piau? State) National Parks, Northeastern Brazil. 112 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 1962 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1101 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 57913 records from Fichier communal des ongul?s. 33 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 25 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 9176 records from R?seau de surveillance Polynesia Mana - Peuplements de poissons. 115 records from Living Cirripedia. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125?m across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Lemyra persephone, a new autumnal species from Yunnan, southwestern China (Lepidoptera, Erebidae, Arctiinae). 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 218 records from Land and freshwater molluscs of Northern Spain. 724296 records from Finnish Floristic Database (Literature Sources). 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 3775 records from Donn?es naturalistes de Charlotte PICARD. 402 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 4 records from Ostracoda abundance of Hole 44-390. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 72176 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 1763 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 230 records from Inventaire avifaune. 28182 records from University of California Santa Barbara Invertebrate Zoology Collection. 22787815 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 277 records from Aunar esfuerzos y recursos t?cnicos, econ?micos y humanos con el fin de adelantar acciones de investigaci?n para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 117 records from Nannofossil abundance of Hole 41-366A. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 100 records from Anfibios y reptiles de la desembocadura del ca?o Teracay en el r?o Tomo, Puerto Carre?o, Vichada - Proyecto Colombia Bio. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 64 records from Lynx 1996 pr?sence Occasionnelle Mailles 10km R?seau Loup-Lynx ONCFS. 5460 records from Colecci?n de Fabales del Museo Bot?nico CORD - IMBIV. 74 records from Nannofossil abundance of Hole 39-359. 85921 records from ALCB - Herb?rio Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 22 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 3 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 6 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 80315 records from Fish specimens of Kagoshima University Museum. 3825 records from UTEP Invertebrates (Arctos). 217 records from Inventaire des odonates 2014. 113 records from Nannofossil abundance of Hole 49-412. 24 records from Abundance of benthos infauna at station PS1240-1. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 50 records from Herpetofauna de la expedici?n Pisba - Proyecto Boyac? BIO UPTC. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 2143 records from Range table from benthic foraminifers in ODP Hole 154-929A. 112 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 267172 records from hymenoptera. 60 records from Amphibian and Reptilian (KIEE-AR). 232 records from Filogenia de las cact?ceas columnares (Pachycereeae) con base en caracteres anat?mico-morfol?gicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79? N section). 5919 records from Cat?logo taxon?mico y biogeogr?fico de los radiolarios (orden Polycystina) de la regi?n central y sur del Golfo de California. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 18 records from Naturtag. 16071 records from Herbier Louis-Marie (QFA) - Collection de lichens. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 130434 records from Herbarium of Taiwan Forestry Research Institute. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 23 records from Ackerrain Pl?nhagen. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Donn?es odonates. 242 records from Malawi-Histeridae-Biodiversity-Data. 1286 records from Planktic foraminifera abundance of Hole 7-64. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Sch?ffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (St?l, 1860) and revalidation of P. fuscescens (Dallas, 1851). 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 7283 records from Colec??o Entomol?gica IIA. 2 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 16763 records from MZFC/Coleccion de Aves. 1190 records from Cole?pteros presentes en un proceso de restauraci?n pasiva en bosque seco tropical. 29601 records from The cryptogamy collection (PC) at the Herbarium of the Mus?um national d'Histoire Naturelle (MNHN - Paris). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 5855 records from Actualizaci?n y depuraci?n de las bases de datos de la Colecci?n Nacional de Helmintos: P085 y Q028. 1297 records from Recensement et distribution Mammif?res marins Guadeloupe Antilles fran?aises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4038 records from Consolidaci?n de la colecci?n de referencia de peces de la Estaci?n Mazatl?n, (ICMyL-UNAM) e implementaci?n de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 272 records from Inventaire malacologique des murs restaur?s en pierre s?che en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyac?. 1068 records from DMNS Egg Collection (Arctos). 2225 records from Donn?es naturalistes d'Ana?s MAS. 862 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 8 records from The Myriapoda & Onychophora collection (MY) of the Mus?um national d'Histoire naturelle (MNHN - Paris). 65 records from Donn?es du/de la naturaliste Thibault Marie Th?r?se provenant de la base de donn?e du SINP ?le-de-France CETTIA. 6 records from Abundance of benthos infauna at station GIK23065-1. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 27254 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 4 records from Planktic foraminifera abundance of Hole 17-166. 283 records from Flux data of NU2_trap (Table A1). 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 2842040 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 5 records from Two new species of Brueelia K?ler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 228 records from Bishop's University Insect Collection (BUIC). 18 records from ALTERECO_2017_12_18. 29 records from Caracterizaci?n Ecol?gica de la Fauna del P?ramo de Frontino o del Sol. 361 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 5346 records from Sediment metagenome. 1702 records from BioGIS - Bryophytes - HUJ collections. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15255 records from Anymals+plants - Citizen Science Data. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 957 records from Collection de longicornes et autres col?opt?res saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 1571 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 849 records from CNAN/Scorpiones. 346 records from Universidad del Valle de Guatemala - Colecci?n de Artr?podos. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2208 records from marine sediment metagenome Raw sequence reads. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 400 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 565 records from Colecci?n Zool?gica Universidad del Tolima (CZUT) - Ar?cnidos. 776 records from Programme ACT : R?partition Pie bavarde 2010 - 2014 Coordonn?es GPS Lambert 93. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9811 records from Colecci?n, preservaci?n y caracterizaci?n de cultivares criollos de origen espa?ol de trigo y centeno de M?xico. 19665 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 44 records from Mam?feros peque?os en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 817 records from Programme ACT : R?partition Tourterelle turque 1997 - 2001 Coordonn?es GPS Lambert 93. 2193 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 243 records from Thistles species and abundance. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 29559 records from Occurrences de vecteurs de maladies recens?es ? l'H?pital de M?nontin. 2111 records from Flora vascular acu?tica de la cuenca del R?o Tames?. 4962 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 66 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservaci?n Guanacaste in northwestern Costa Rica, with a key to their identification. 120 records from BIRDRACE The early birds. 1933 records from Donn?es odonates collect?es par le CEN Aquitaine entre 1995 et 2015. 5 records from Two new nematode species of the genus Tobrilus Andr?ssy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 88 records from Type locality records of Polycystididae species in the world. 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 173403 records from Base de datos de plantas vasculares del Pa?s Vasco: ARAN-EH. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 1096 records from Donn?es naturalistes de St?phane ORIO. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 2 records from Donn?es de L?pidopt?res de Bruno DAUGET - D?pt des PYRENEES-ORIENTALES (66). 26295 records from JCT AVH data. 1044940 records from CLICNAT Base de donn?es naturaliste picarde g?r?e par Picardie Nature. 37580 records from DATAVES. 41 records from Planktic foraminifera counts of sediment core V28-128. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 179 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 7 records from Planktic foraminifera abundance of Hole 53-418B. 31 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 14 records from Berea College, Ralph L. Thompson Herbarium. 3224 records from Amphibiens de Guyane. 134 records from Nannofossil abundance of Hole 7-62A. 409 records from Distribution of nanoplankton at trap WR2. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 11 records from Nannofossil abundance of Hole 9-82. 9 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 642 records from An?lisis de la biodiversidad y servicios ecosist?micos para su aplicaci?n en la toma de decisiones en el departamento de Boyac?/Boyac? Bio-Flora El Consuelo. 24 records from Planktic foraminifera abundance of Hole 20-200A. 575 records from Nannofossil abundance of Hole 75-530A. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 5 records from Collection Myriapoda - SNSD. 1857 records from Censo de aves acu?ticas nidificantes de la Comunidad Aut?noma del Pa?s Vasco. 78612 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1035 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 714 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 17 records from Marine metagenome ICM_AGW. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 78 records from Donn?es de la naturaliste Anna Even. 3546 records from Dorset SW Pilot species dataset. 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 9 records from Benthic macrofauna abundance of sediment core 13077-087. 816 records from Esp?ces v?getales sur sable roux du fourr? de Ranobe, PK 32 Toliara. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 100 records from (Table 5) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the Lesches en Diois section. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 81 records from Kystfuruskoger i Tysnes og Fusa. 992 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 4 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avan?ats de Blanes, Macroinvertebrados Limno. 87 records from Diatom abundance of Hole 95-613. 2364 records from Modelaci?n de la distribuci?n geogr?fica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 1 records from Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini. 35 records from Inventaire et suivi de la faune ?cras?e. 1000 records from nsmk_mm_2019. 47 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 23 records from Abundance of benthos infauna at station GIK23042-2. 68 records from Streuobstwiese. 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 317 records from Benthic foraminifera and algae abundance of Hole 81-554A. 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 82 records from R?ckkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 ?m fraction. 247 records from Flora vascular y no vascular: expedici?n Cuenca Media del r?o Chicamocha - Proyecto Boyac? BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 982 records from Diatom assamblage in samples from sediment trap OG4. 765 records from DAR AVH data. 2779607 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 170543 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 349 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 41 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 1009 records from Programme ACT : R?partition Merle noir 2012 - 2016 Coordonn?es GPS Lambert 93. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris ?ur?i?. 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 4616 records from Inventaire de la flore du Grand Poitiers 2009. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 4 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 1461 records from M. Gollop Collection. 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 3350 records from Reef Check in Taiwan ???????. 1 records from Donn?es naturalistes d'Olivier DELZONS. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 836 records from Colecci?n Ornitol?gica de la Universidad Tecnol?gica del Choc?. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 1 records from New morphological information on Simulium wygodzinskyorum Coscar?n & Py-Daniel, 1989 (Diptera: Simuliidae). 16 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 95 records from Conocimiento de la diversidad y distribuci?n actual del ma?z nativo y sus parientes silvestres en M?xico (Tamaulipas). 1120 records from Programme national de science participative sur la Biodiversit? Littorale (BioLit). 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartem?wen. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 538 records from Composici?n flor?stica y estructura de una parcela permanente en bosques h?medos tropicales del municipio de Pie de Pepe, Choc?. 1028 records from Nannofossil abundance of Hole 94-607. 27 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 2081 records from Thrips (Thysanoptera) in Norway. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2497 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 18 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 614 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 18 records from Anfibios presentes en el Cerro J?nano. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 120 records from Donn?es esp?ces - Expertise IPE 79. 1715184 records from NBIS Records to December 2016. 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 27 records from Planktic foraminifera abundance of Hole 51-417B. 105 records from Lynx 2015 pr?sence Occasionnelle Mailles_10km_LAEA R?seau Loup-Lynx ONCFS. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 13 records from Benthic foraminifera abundance of Hole 96-620. 99 records from Nanoplankton abundance at station GeoB2006-4. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 319 records from Donn?es naturalistes de Monsieur LEFEBVRE Fran?ois. 1543 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 1716 records from Marine algal flora of Flores and Corvo Islands, Azores. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 611 records from Donn?es du R?le gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 163 records from Relative abundance of coccosphere-units at site GIK23414. 33 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 292 records from Monitoreo y recolecci?n de la diversidad de razas de ma?z criollo en la regi?n de la Huasteca en M?xico para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 688 records from donn?es arachnologiques de CARR David. 19 records from Fishes from the Auckland and Campbell Islands, Cape Expedition, 1942-1944. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 4 records from Nannofossil abundance of Hole 3-22. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 884 records from Diversit? et distribution de quelques esp?ces de plantes agroforesti?res au B?nin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), esp?ce calcicole end?mique de la Polyn?sie fran?aise, d?crite de l?atoll soulev? de Niau (Tuamotu). 1170 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 5 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 134 records from BIRDRACE Griffin Wood Warblers. 15 records from Nannofossil abundance of Hole 10-93. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 1422 records from Donn?es du/de la naturaliste Chevreau David provenant de la base de donn?e du SINP ?le-de-France CETTIA. 122 records from Base de datos de las especies maderables del g?nero Dalbergia en M?xico, registros del Herbario Nacional de M?xico (MEXU). 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 38 records from Ours 2006 pr?sence Occasionnelle Mailles 10km LAEA R?seau Ours brun ONCFS. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 275 records from Planktic foraminifera counts of sediment core V14-77. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 80300 records from CUMV Fish Collection. 7 records from New Oligaphorura species (Collembola: Onychiuridae) from the forests of East Asia. 2826 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 931 records from South American Antarctic Marine Biodiversity Literature. 6922 records from MUST, Insecta. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 57 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 1026846 records from Donn?es ONF faune-flore-fonge. 81 records from M?tropole_Nice_C?te_d'Azur_2017_12_18. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 1 records from A taxonomic study on the Bornean and Philippines Sword-tailed Crickets in the genus Rhicnogryllus Chopard, 1925 (Orthoptera: Trgonidiidae; Trigonidiinae). 911 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 51 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 50 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 48 records from Deutsche Schule Budapest. 1463 records from Regroupement de donn?es rhopaloc?res r?colt?es sur la p?riode de 2010-2015 par Cistude Nature. 1930 records from Donn?es de la naturaliste Lemoine Delphine provenant de la base de donn?e du SINP ?le-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 713 records from Modelaci?n de la distribuci?n y abundancia de las subespecies de venado cola blanca en M?xico: implicaciones de conservaci?n y manejo. 2 records from Stenus maculifer CAMERON: eine B?chse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 384 records from Marine metagenome ICM_AWP. 3579 records from The reptiles and amphibians collection (RA) of the Mus?um national d'Histoire Naturelle (MNHN - Paris). 79056 records from University of Michigan Museum of Zoology, Division of Mollusks. 3 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 121 records from Foraminifera abundance of sediment core IN68-28. 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 2 records from New records of Nuuanuidae (Crustacea: Amphipoda: Senticaudata) from Korean waters, with descriptions of one new genus and two new species. 32 records from Site Condition Monitoring of the downy willow Salix lapponum component of the Vascular Plant Assemblage interest of Skinsdale Peatlands SSSI, 2016. 122 records from M. Burton (1936). The Fishery grounds near Alexandria IX ? Sponges. Notes and Memoirs No.17. Department of Zoology, British Museum. Fisheries Research Directorate. Ministry of Commerce and Industry, Egypt.. 5 records from Occurrence of mammalia relicts at site Siebenlinden 3. 19651 records from Estudios bi?ticos (Plantas, Fauna Ed?fica, Anfibios y Aves) en los Complejos de p?ramos Tota-Bijagual-Mamapacha. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 275 records from Range table from benthic foraminifers in ODP Hole 144-874B. 29912 records from Donn?es acquises via le r?seau du Conservatoire botanique national du Bassin parisien. 6322 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, M?xico. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 62157 records from DASSH Data Archive Centre Academic Surveys. 98 records from Donn?es opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (O?maritz). 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 14980 records from Donn?es Entomologiques A. HORELLOU 1988-2018. 96 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 285 records from Donn?es du/de la naturaliste Cousin Richard provenant de la base de donn?e du SINP ?le-de-France CETTIA. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 540 records from Foraminifera abundance of Hole 74-526A. 48 records from ZUEC-ECH - Cole??o de Echinoidea do Museu de Zoologia da UNICAMP. 1435 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis H?bner (Lepidoptera: Tortricidae). 1 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 600 records from Colecci?n de Herpetolog?a de la Universidad del Quind?o (HERPETOS-UQ). 292277 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herb?rio Virtual REFLORA. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 5 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 237 records from Planktic foraminifera abundance of Hole 21-207. 11 records from Donn?es naturalistes de Thibault RAMAGE. 7 records from A revision of the systematics and distribution of the damselfly genus Prodasineura Cowley, 1934 (Odonata: Zygoptera: Platycnemididae) in Vietnam with description of two new species. 15 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 43 records from Vogelstimmenf?hrung durch den Tiergarten. 448 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 11321 records from WOLL AVH data. 1 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 203 records from Insectos de la expedici?n al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 84 records from Ostracoda abundance of Hole 48-403. 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 34 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 2975 records from Tetr?podos de Uruguay. 564 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 4 records from Craspedotropis gretathunbergae, a new species of Cyclophoridae (Gastropoda: Caenogastropoda), discovered and described on a field course to Kuala Belalong rainforest, Brunei. 1 records from Phylogenetic analysis and systematic position of two new species of the ant genus Crematogaster (Hymenoptera, Formicidae) from Southeast Asia. 2714 records from Donn?es de la R?serve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donn?e du SINP ?le-de-France CETTIA. 195 records from Donn?es de la naturaliste Giordano Charlotte provenant de la base de donn?e du SINP ?le-de-France CETTIA. 3 records from Larval morphology and life history of Eutrichosoma mirabile Ashmead and description of a new species of Eutrichosoma (Hymenoptera, Chalcidoidea). 22 records from Propri?t? r?gionale du Moulin des Marais - Inventaire naturaliste 2015. 94 records from Caddisflies (Insecta: Trichoptera) from Maranh?o State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 12 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 4 records from The Haliplidae (Coleoptera) of Atlantic Canada: new records, distribution, and faunal composition. 7 records from Three new species of the genus Mimetus Hentz, 1832 (Araneae: Mimetidae) from Yunnan-Guizhou Plateau of China. 7529 records from University of Kentucky Insect Collection. 51788 records from Atlas des Orthopt?res et Mantides de France m?tropolitaine. 35 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 64 records from Donn?es du/de la naturaliste Bourdin Dominique provenant de la base de donn?e du SINP ?le-de-France CETTIA. 2 records from A remarkable burrow-dwelling alpheid shrimp, new genus and new species, from the tropical eastern Pacific (Malacostraca: Decapoda: Caridea). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 1418 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 2497 records from Donn?es des collections d'algues du MNHN. 2329 records from SP-Algae - Herb?rio do Estado "Maria Eneyda P. Kaufmann Fidalgo - Cole??o de Algas. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 1 records from Description of Metarhabditis giennensis sp. n. (Nematoda, Rhabditida, Rhabditidae) from decaying wood of a riverbank forest in the southern Iberian Peninsula. 422108 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammif?res marins Guadeloupe Antilles fran?aises (AET). Suppl?ments. 118 records from Observation des insectes sur le territoire de la M?tropole Rouen Normandie. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 24 records from Ostracoda abundance of Hole 48-406. 391 records from GEOECOLINK_2017_12_18. 2 records from Updates to the bee fauna of Portugal with the description of three new Iberian Andrena species (Hymenoptera: Apoidea: Anthophila). 106 records from Distribution of planktic foraminifera (125-250 ?m) of box sediment core PS1246-2. 16 records from Hazel Dormouse in Ireland. 1218 records from UTEP Herpetology Osteology (Arctos). 16 records from A survey of Agroeca Westring, 1861 from China (Araneae: Liocranidae). 135998 records from The Scottish Squirrel Database. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 272 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 2 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 143 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 29 records from Ours 2004 pr?sence Occasionnelle Mailles 10km LAEA R?seau Ours brun ONCFS. 829 records from Programme ACT : R?partition Geai des ch?nes 2007 - 2011 Coordonn?es GPS Lambert 93. 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 60 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 1 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 40 records from Planktic foraminifera abundance of Hole 14-137. 306 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 2459 records from UWYMV Bird Collection (Arctos). 751 records from Donn?es naturalistes de Monsieur JOURDE R?mi. 873 records from Programme ACT : R?partition Geai des ch?nes 2008 - 2012 Coordonn?es GPS Lambert 93. 231 records from Epifauna community at Waarde and Saeftinghe (Westerschelde) in 1991. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 1822 records from Galathea II, Danish Deep Sea Expedition 1950-52. 380 records from UWYMV Herpetology Collection (Arctos). 160 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 14069 records from Midden-Limburg Fish Ponds Survey. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 64150 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 1 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 2 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 411 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 895 records from Geometridae de France m?tropolitaine. 7396 records from Colec??o Entomol?gica do Museu de Hist?ria Natural de Maputo. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 174 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 188 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 724 records from Heritage Trees of Ireland. 24 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 613 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 403 records from Collection Polychaeta - ZSRO. 16774 records from imr_mareano_rpsledge. 140 records from Donn?es du/de la naturaliste LUPOLI ROLAND provenant de la base de donn?e du SINP ?le-de-France CETTIA. 200 records from Bats of Kim Hy Natural Reserve, Vietnam. 41661 records from Herbario de la Facultad de Ciencias Biol?gicas de la Universidad Complutense de Madrid (MACB). 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 880 records from Diversity of Spiders from Azorean Trails. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 8 records from RISC Non-Native Species Records for Zebra Mussel. 139 records from Nannofossil abundance of Hole 55-433. 2 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 10354 records from Inventaire de la flore de Charente-Maritime 2018. 2012 records from Pollen profile RAC20, Lake Racou, France. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 14 records from Revalidation and taxonomic revision of Teloneria Acz?l (Diptera, Neriidae), with description of two new species. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 93 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 214 records from Freshwater fish records via iRecord - additional species. 10283 records from Inventario de Hymen?ptera; paras?tica en M?xico. 20 records from Abundance of benthos infauna at station GIK23055-1. 1 records from Description of a new whitefly? Pealius satakshiae Dubey (Hemiptera: Aleyrodidae) ? infesting Quercus leucotrichophora (Fagaceae) in the Western Himalaya? India. 374 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 8561 records from Colecci?n de insectos agr?colas del proyecto diversidad en sistemas de cultivos. 6 records from Benthic macrofauna abundance of sediment core 13200-017. 1785 records from 3Soil16S. 1 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 715 records from Museu Valenci? d?Hist?ria Natural - Fundaci?n Entomol?gica Torres Sala: FETS. 4345 records from Gunma Museum of Natural History, Fungi Specimen. 9 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 2 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 30 records from Nannofossil abundance of Hole 24-233A. 33235 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 12558 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 422 records from Percentages of planktonic foraminifera species in sediment core V22-38. 24 records from Dinoflagellate abundance of Hole 28-274. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 4 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 50 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 1 records from A new brachypterous Filchneria and two new generic records for China, Arcynopteryx and Pictetiella (Plecoptera: Perlodidae). 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribuci?n de la Nutria (Lontra longicaudis) en la cuenca baja del r?o Sin? en el departamento de C?rdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 276 records from Birds Specimens of Akita Prefectural Museum. 516 records from Planktic foraminifera counts of sediment core A15-558. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 100 records from Donn?es naturalistes de LE GLOANEC Vincent. 177831 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-78. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 185 records from Size of planktic foraminifera at CTD station PS55/051. 2 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 102 records from Organochlorine and total mercury in bivalve Anadara tuberculosa and other species from the Nicoya Gulf, Costa Rica in 1988. 1658 records from ZUEC-HEM - Cole??o de Hemiptera do Museu de Zoologia da UNICAMP. 7122 records from Whale catches in the Southern Ocean. 160952 records from UWFC Ichthyology Collection. 813 records from Programme ACT : R?partition Tourterelle des bois 1996 - 2000 Coordonn?es GPS Lambert 93. 70 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 27 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 26 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 1 records from A new species of Novastoa Finlay, 1926 (Mollusca: Gastropoda: Vermetidae) from coral reefs of the Pacific Ocean. 230 records from Biometr?a peces Parque Nacional Natural La Paya. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 13868 records from Donn?es faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-V?gel (VFV). 5232 records from EDP Foz-Tua: Vascular Flora ? Complementary Studies and Baseline Year of the Ecological Monitoring Program [2011]. 53 records from Donn?es du/de la naturaliste Dubois Yves provenant de la base de donn?e du SINP ?le-de-France CETTIA. 2 records from Bracon planitibiae sp. nov. (Hymenoptera: Braconidae), a new parasitoid of Asian longhorned beetle (Anoplophora glabripennis). 2 records from A new genus and species of Onciderini Thomson, 1860 (Coleoptera: Cerambycidae: Lamiinae) from Ecuador, with notes on additional taxa. 42 records from Occurrence of mammalia relicts at site l?Abri de Campalou. 73340 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 51 records from Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa. 76 records from Schulgel?nde des Gymnasiums Nepomucenum (Coesfeld). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paran? basin, Brazil. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 130 records from Total foraminifera counts of multinet M21/6_MSN784. 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 1 records from Redescription of Lernaeenicus stromatei Gnanamuthu, 1953 (Copepoda: Siphonostomatoida: Pennellidae) infesting the Black Pomfret Parastromateus niger (Bloch) from Indian waters. 102 records from Benthic foraminifera abundance of Hole 42-372. 1369 records from HUCPE - Herb?rio da Universidade Cat?lica de Pernambuco. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 31 records from Bulletin d'informations de l'Association fran?aise de Lich?nologie. 38 records from Nannofossil abundance of Hole 10-89. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 91 records from Nannofossil abundance of Hole 30-285A. 469920 records from Natural England Marine Monitoring surveys. 682 records from Range table from benthic foraminifers in ODP Hole 139-857A. 81 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 23648 records from WTSWW Data: All Taxa (West Wales). 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 126 records from Foraminifera species abundances from tow TT011_10-MOC71. 10 records from Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 2867 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 17 records from Leptoclinides (Ascidiacea, Didemnidae) from Brazil: new records and two new species. 94 records from Range table from planktonic foraminifers in ODP Hole 170-1040B. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 10167 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 1 records from Amphicnemis rigiketit sp. nov. from Sarawak, with notes on Amphicnemis remiger Laidlaw, 1912 (Odonata: Zygoptera: Coenagrionidae). 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 1584 records from Coleoptera Collection. 183 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 6433 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 403 records from Loup 2016 pr?sence occasionnelle communale (r?seau Loup-Lynx ONCFS). 1429 records from Kangawalla Bird Sightings. 601 records from Muestreos y recolectas de flora end?mica y casi-end?mica de matorral costero y chaparral de la zona mediterr?nea Baja California, M?xico. 20 records from Occurrence of mammalia relicts at site Niederlehme. 1264 records from Grand Voyeux - Suivis scientifiques. 38 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 86 records from UWIZM Cnidarians. 231 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 5 records from Four new species and new records of Manota (Diptera: Mycetophilidae) from Sulawesi, Indonesia. 299 records from Colecci?n Taxon?mica Nacional de Insectos ?Luis Mar?a Murillo? (CTNI). 2184 records from Occurrence (present/absence) and abundance of zooplankton in Murchison Bay, Lake Victoria. 23 records from Ours 2016 pr?sence Occasionnelle Mailles 10km LAEA R?seau Ours brun ONCFS. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 371 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoT? KL71. 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 1135 records from Cole??o Zool?gica de Refer?ncia da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 22 records from Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex. 3 records from Description of a new species of Ochraethes Chevrolat, 1860, redescription of Plocaederus mirim Martins and Monn?, 2002, and new geographical records for Plocaederus Dejean, 1835 (Coleoptera, Cerambycidae, Cerambycinae). 66 records from SNH Invertebrate Site Condition Monitoring 2013/14: Whitlaw Mosses SSSI. 14341 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 174667 records from Tasmanian Museum and Art Gallery provider for OZCAM. 938 records from TTRS Mammals. 213 records from DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 6 records from Neotropical Chvalaea Papp & F?ldv?ri (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 4 records from Discovery of a new species of Embolemus Westwood (Hymenoptera: Embolemidae) from New Caledonia. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 1232 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling at Pathogen Plots]). 38 records from Colecci?n Ornitol?gica Universidad de la Amazonia. 45 records from Brown bear monitoring data from Deosai National Park. 669 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 2171 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part II. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 39619 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Scorff river (France). 1 records from Toward a revision of the bamboo corals: Part 1, species in the Muricellisidinae (Octocorallia: Isididae). 2 records from Meschia zoui sp. nov., first representative of the family Meschiidae from China (Hemiptera: Heteroptera: Lygaeoidea). 93662 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 8 records from Genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) from Laos, with descriptions of five new species. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Occurrence of mammalia relicts at site High Furlong. 53961 records from Long-Term Monitoring Network Vegetation Quadrats. 36 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-K?stner-Schule erforscht das Bachemer Wiesental. 16 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 1254 records from Bryozoa, Brachiopoda and Entoprocta from the collection of the Arctic University Museum of Norway in Troms?. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1 records from A new miniature Melanesian Forest Frog (Ceratobatrachidae: CORNufeR) from New Britain Island, constituting the first record of the subgenus BATRAchylOdes from outside of the Solomon Archipelago. 29 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 120 records from Collection Crustacea ZMG. 3 records from Revision of Chinese mainland Hybovalgus Kolbe, 1904, with description of a new species, and Excisivalgus Endr?di, 1952 reduced to synonymy with Hybovalgus (Coleoptera: Scarabaeidae). 83 records from Naturpark Kottenforst-Ville 16.6.09. 1 records from Spirlins of the southern Black Sea basin, with the description of a new species (Teleostei: Leuciscidae). 134 records from Faunal assemblage of sediment core TR149-32. 699 records from Planktic foraminifera abundance of Hole 15-154A. 787 records from Programme ACT : R?partition Pie bavarde 2009 - 2013 Coordonn?es GPS Lambert 93. 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 5 records from Inventaire des sangsues - d?termination des ?chantillons de l'enqu?te participative - Subvention UMS Patrinat. 1293 records from Flora gen?rica de las gram?neas del estado de Tlaxcala. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pf?lzerwald. 5464 records from Natural History Museum Maastricht (NL) - Herbarium. 9384 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio S?o Francisco basin, southeastern Brazil. 352 records from Loup 2015 pr?sence occasionnelle communale (r?seau Loup-Lynx ONCFS). 11 records from Review of the genus Prays H?bner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 161 records from Total foraminifera counts of multinet SO117_MSN1244. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 8956 records from Formaci?n de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 6 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 69 records from Entdeckertour am Muldestausee 1/05. 613 records from Implementaci?n de la bioindicaci?n en el R?o Cauca - 2016. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 2534 records from Elaboration de table de tarif de cubage multisp?cifique (I). 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulid?es d'Europe. 521 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 122 records from BIOTOPE_2017_12_18. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 108 records from BIRDRACE Diesmal sehen wir mehr. 16 records from Insect Collections of Okomu National Park- Nigeria. 1098 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 279489 records from ARABEL - Arachnologia Belgica. 133650 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 26 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1763 records from Arachnida of Costa Rica (INBio). 675 records from Donn?es du naturaliste RADOGEWSKI Alain provenant de la base de donn?e du SINP ?le-de-France CETTIA. 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 3132 records from Ross A. Layberry, Collection. 2 records from A new species of Mesochra (Copepoda: Harpacticoida: Canthocamptidae) from a coastal system of northern Colombia with a key to the American species. 348 records from Antarctic pycnogonids. 60949 records from MLZ Bird Collection (Arctos). 50 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 256 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 361010 records from Seasearch Marine Surveys in England. 35 records from Planktic foraminifera abundance of Hole 84-566C. 9 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 56 records from A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea. 75 records from Naturpark Kottenforst-Ville 19.6.09. 5 records from Four new genera of Schizopteridae (Hemiptera: Heteroptera) from theAfrotropical and Neotropical regions. 228 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 2963 records from Collection Trichoptera - SMF. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 3 records from A new pygmy species of box jellyfish (Cubozoa: Chirodropida) from sub-tropical Australia. 51 records from Genotipificaci?n de especies de la ictiofauna del Sistema P?nuco-Tames? a trav?s de la generaci?n del c?digo de barras de ADN mitocondrial. 795 records from UCBG TAPIR Provider. 18 records from ZUEC-CNI - Cole??o de Cnidaria do Museu de Zoologia da UNICAMP. 136 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/042-2. 6057 records from Banco de datos de la ictiofauna del R?o Bravo desde 1902 a 1992 en la colecci?n ictiol?gica de la UANL. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 69 records from Montana State University - Billings. 353 records from Contribuci?n a la distribuci?n, ecolog?a y estado de conservaci?n de dos especies del g?nero Sceloporus, end?micas de la regi?n del Cabo, Baja California Sur. 333 records from renaturierter Main (Kemmern bei Bamberg). 751 records from Planktic foraminifera abundance of Hole 27-262. 1798 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 35 records from Planktic foraminifera abundance of Hole 27-260. 126351 records from Arizona State University Hasbrouck Insect Collection. 625 records from Geochemistry and sedimentology on core POS200/10_28-1. 445 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 77 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3361 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetol?gica Chetumal). 124 records from Birdrace-Die_Ackerm?nnchen-Schalm-Eder-Kreis. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 1480 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3960 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 9446 records from Batsites inventory for England (1949-2011). 59016 records from Isopoda (Interim dataset). 1 records from A new epigean species of the genus Anelpistina (Insecta: Zygentoma: Nicoletiidae) from Sierra de El Abra, Taninul, Mexico. 190 records from Plant macrofossil concentrations from an open section of Lac de Fully sediments. 5 records from A survey of East Palaearctic Gnaphosidae (Araneae). 10. Three new Gnaphosa species from the Dzhungarian Alatau Mountains (Eastern Kazakhstan). 89 records from Microbes in drinking water and biofilms (18S rDNA amplicon study). 678 records from Ortopteroides de Oaxaca, M?xico: Orthoptera, Mantodea y Phasmatodea. 457 records from Helmintos par?sitos de peces dulceacu?colas de cuencas hidrol?gicas del Centro-Norte de M?xico (Durango). 250323 records from Donn?es faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 87901 records from MDFRC macroinvertebrate survey. 177 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 474 records from Donn?es du/de la naturaliste VINCENT Sylvain provenant de la base de donn?e du SINP ?le-de-France CETTIA. 128 records from Inventaire des reptiles 2014. 2889 records from Algae collection, Oslo (O), Natural History Museum, University of Oslo. 589 records from Programme ACT : R?partition Pie bavarde 2005 - 2009 Coordonn?es GPS Lambert 93. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 29412 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 5 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 6 records from Nannofossil abundance of Hole 6-49. 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 9373 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 43 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 5061 records from Metagenome from mudbank Area,Alappuzha Kerala India. 2 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 72 records from Planktic foraminifera abundance of Hole 16-161. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 7029 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 4853 records from Inventaire des esp?ces v?g?tales du sous bois des plantations de Teck de la for?t naturelle de la Lama. 323 records from Eco-Strat?gie_2017_12_18. 952 records from Guinea-Bissau Herpetological Collection - IICT. 411 records from SuLaMa reptile survey I 2012. 1 records from Psilotris vantasselli, a new species of goby from the tropical western Atlantic (Teleostei: Gobiidae: Gobiosomatini: Nes subgroup). 61 records from Shrews of Poland. 967 records from Inventaire des Odonates. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 9 records from Nannofossil abundance of Hole 2-11. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 75 records from (Table 3) Downcore distribution of live benthic foraminifera of sediment core SW_2b, California continental borderland. 906 records from C?digos de barras del ADN de mam?feros topotipos de M?xico Fase I: Noroeste mexicano. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 186 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 2371 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 238 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 15 records from Nannofossil abundance of Hole 6-48B. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 2 records from A new species of Schindler's fish (Teleostei: Gobiidae: Schindleria) from the Malay Archipelago (Southeast Asia), with notes on the caudal fin complex of Schindleria. 5229 records from European Moth Nights. 172 records from Donn?es du/de la naturaliste Roquinarc'h Oc?ane provenant de la base de donn?e du SINP ?le-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 6775 records from Donn?es du naturaliste MIGUET Pierre provenant de la base de donn?e du SINP ?le-de-France CETTIA. 85 records from Planktic foraminifera counts of sediment core V27-47. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 1462 records from Colecta bot?nica: ?rea maya regi?n de la Reserva Calakmul, Campeche. 22 records from Revision of the Oriental Chaetocnema species (Coleoptera, Chrysomelidae, Galerucinae, Alticini). 8 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 2190 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 1036 records from BUND - Dassower See (L?beck/Dassow). 59978 records from Donn?es naturalistes de Monsieur Fran?ois FOURNIER. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 383 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 54016 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 102 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2012. 4 records from S?chsische Schweiz (Wehlener Gebiet). 23 records from AlgaTerraMovies. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 6990 records from Ethnobotanical surveys species in Benin (West Africa). 87 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 5576 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 3435 records from Benthos Chirnov Basin 1986 and 2002. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 6387 records from Donn?es naturalistes de Monsieur LAFAGE Denis. 5 records from On the genera Ptiloneura Enderlein, Loneura Nav?s, and Loneuroides Garc?a Aldrete (Psocodea: ? Psocoptera?: Ptiloneuridae). 51 records from Coccoliths in sediment core GIK23065-3. 133 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 708 records from EDP Baixo Sabor: Herpetology ? Baseline Studies [2009]. 14 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 90 records from Actualizaci?n de la base de datos de la Colecci?n nacional mexicana de cultivos microbianos. 127 records from Freshwater crustaceans in Antarctic and sub-Antarctic lakes. 2141 records from University of Amsterdam (NL) - P?ramo Vegetation Research, National Natural Park El Cocuy, Colombia. 23675 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 17 records from Analyses of the recent components of sediment core PS1219-1. 365 records from HBRG Invasive Non-native Plants Dataset. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 3240 records from Inventario flor?stico de la Sierra de Huautla, Morelos. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 186671 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 35 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Par?, Brazil. 16253 records from Birds Specimens. 468 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : donn?es esp?ces non cibles pi?g?es. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 56 records from Planktic foraminifera abundance of Hole 23-227. 18107 records from DMNS Mammal Collection (Arctos). 43 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 64 records from Bats of northeastern Vietnam. 1028 records from IBF Monitoring of Fungi. 231 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 2380 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 1809 records from BenthosChukchiFN762_1976_Falk5. 944 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 33 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 89 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 70 records from Donn?es 2017 de l'Observatoire de la Biodiversit? des For?ts. 23449 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 240 records from Knechtweide (Kohlfurth). 3238 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 90 records from MCP-Mamiferos - Cole??o de Mam?feros. 11 records from Benthic macrofauna abundance of sediment core 12930-073. 336 records from Stable isotope data and sedimentology of core SO42-74KL. 89 records from Meniscus Midges (Dixidae) of Ireland. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 286 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1748 records from Occurrence database of native plants and animals of south-central Chile. 259 records from Natura 2000 Parc naturel r?gional de Lorraine. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 208 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 2 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 2271 records from Helmintos par?sitos de peces del sureste de M?xico. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 81 records from BCCM/ULC Cyanobacteria culture collection at the University of Li?ge (ISO9001 certified). 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 353 records from Donn?es naturalistes de Hubert GUIMIER. 1800 records from Donn?es de la collection Rousset -1947-2013. 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 874 records from Programme ACT : R?partition Grive musicienne 2004 - 2008 Coordonn?es GPS Lambert 93. 134 records from Lynx 2005 pr?sence Occasionnelle Mailles 10km R?seau Loup-Lynx ONCFS. 87 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 133 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 1 records from Schulman's Neotropical Adelobotrys database. 12094 records from Amino acid addition experiment Metagenome. 3131 records from Donn?es DREAL Centre-Val de Loire - Faune - 2018. 48476 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9349 records from Harriet Irving Botanical Gardens (HIBG). 7 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 46092 records from Weed and native flora data for the Swan Coastal Plain. 62 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1455 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3079 records from Insectes Hym?nopt?res Scollid?s de France. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 1197 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 916 records from IOW Natural History & Archaeological Society Marine Records. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 6189 records from Fauna y flora en ?reas con cultivos de palma de aceite en el norte y oriente de Colombia. 14 records from Occurrence of mammalia relicts at site Climauti II. 140 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 135 records from Waldi-Weiher. 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingm?hle. 25 records from Donn?es de NICOLAS Vincent (SAPROX). 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 1 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 77 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 121 records from Etude ?cologique du Parc des Lilas (94). 12 records from Donn?es bibliographiques ASFRA. 7953 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 1 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 2340 records from Butterflies of Singapore and Peninsular Malaysia (Nymphalidae). 7510 records from Base de datos de las gram?neas (Poaceae) del noreste de M?xico. 4036 records from Inventario de larvas de peces en la regi?n sur del Golfo de California (GAP 81, 85 y 86) y en el Pac?fico Tropical Mexicano (GAP 88-91). 254 records from Atlantic Forestry Centre Insect Reference Collection. 4722 records from Dataflos. 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 2743 records from marine sediment metagenome Raw sequence reads. 9 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 115 records from Total foraminifera counts of multinet M21/4_MSN694. 46 records from An der Ohm, (Wettsaasen). 2 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 433 records from pins. 2 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 185 records from Inventaire des odonates d'int?r?t communautaire. 14 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los r?os Bita, Manacac?as y Cravo Sur - SULU II. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 149 records from Restauraci?n de flora y repoblamiento de fauna nativa en 1,000 hect?reas para el restablecimiento del corredor biol?gico costero en la Laguna Madre, Tamaulipas. 1893 records from Donn?es de la collection de Hubert Piguet - Famille des Elateridae. 740 records from FBIP: Baboon spider distribution records from selected South African museums. 2419 records from Flora de las sabanas inundables de las cuencas de los r?os Bita, Manacac?as y Cravo Sur - SULU II. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 685 records from Range table from benthic foraminifers in ODP Hole 151-913B. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 259 records from Programme ACT : R?partition Alouette lulu 2009 - 2013 Coordonn?es GPS Lambert 93. 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 2102 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales ?Florentino Ameghino?, Santa Fe, Argentina - Colecci?n Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 16838 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 3 records from Record of the Non-native Suckermouth armored catfish hybrid Pterygoplichthys pardalis (Castelnau, 1985) x Pterygoplichtys disjunctivus (Weber, 1991) (Siluriformes: Loricariidae) in Honduras. 1023 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 7839 records from Inventario flor?stico de la regi?n Calakmul-parte baja de la regi?n Lacandona (Cuenca alta del Usumacinta y Marqu?s de Comillas). 9 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 5316 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 5 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 5314 records from Dados da ocorr?ncia de plantas lenhosas em um gradiente de perturba??o/precipita??o em ?rea de Caatinga, Parque Nacional do Catimbau, Bu?que, PE, Brasil. 11110 records from Royal Ontario Museum Fungarium (TRTC). 3188 records from Butterfly_conservation_2017_12_18. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 27 records from Laubwald Dreil?ndereck (Aachen/Vaals[NL]). 137476 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 1 records from First record of the genus Chandleriella Hlav?? (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 1 records from Scissurella nesbittae, new species, from the Gries Ranch Formation, Lewis County Washington State (Gastropoda: Vetigastropoda: Scissurellidae). 64 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 14 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 28631 records from Donn?es bibliographiques et opportunistes Odonates issues du SIRF. 2736 records from Mise en place d'un suivi scientifique des amphibiens pour la production d?indicateurs de biodiversit?. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 502 records from Metagenome microbial communities of bottom sediments of the Kara Sea. 99 records from D?ne am Ulvenberg (Darmstadt). 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 330 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 2630 records from Swiss Psyllid (Hemiptera) Collections - Basel. 12 records from Four new species of Plumachaetas Salmon (Collembola: Entomobryoidea) from Oceania with comments on the genus and a key to species. 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 16 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 982 records from Pilotoverv?king av dragehode Dracocephalum ruyschiana. 967 records from Planktic foraminifera abundance of Hole 15-148. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 10766 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 260 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 4 records from Herbarium Senckenbergianum (FR) - Protista. 4294 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 172 records from Mollusca specimens of Kuroshio Biological Research Foundation. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 68910 records from Donn?es de l'Observatoire de la Faune de Bourgogne. 425 records from donn?es bibliographiques diverses (non araign?es). 1184 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 255 records from Programme ACT : R?partition Perdrix rouge 2009 - 2013 Coordonn?es GPS Lambert 93. 4389 records from Colecci?n Herpetol?gica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 539 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 2398 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 197 records from Museu de Ci?ncies Naturals de Barcelona: MCNB-Tissue. 320 records from Echinoderms from the Seaflower Biosphere Reserve. 22 records from New records of ant species from Yunnan, China. 22 records from Taxonomy of Ecuadorian water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae). 198 records from Programme ACT : R?partition Alouette lulu 1996 - 2000 Coordonn?es GPS Lambert 93. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 95 records from Nannofossil abundance of Hole 22-217. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 1 records from First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rond?nia, western Amazonia, Brazil. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 117 records from Nannofossil abundance of Hole 49-408. 83 records from Total foraminifera counts of multinet M21/5_MSN728. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 17 records from Analyses of the recent components of sediment core PS1011-1. 6402 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 24 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 2 records from Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China. 2 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 85 records from Donn?es esp?ces - Expertise IPE 123. 29 records from MVZ Herp Observations (Arctos). 64 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 50 records from Beetles on polypores at 4 sites in Norway. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 1224 records from Microbial diversity associated with copepods in the North Atlantic subtropical gyre. 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 1658 records from Relative abundances of twenty-eight dominant benthic foraminifera species of DSDP Hole 23-219 (Table 1s). 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 7 records from Sponge fauna of the New Siberian Shoal: biodiversity and some features of formation. 6 records from Foraminifera abundance of Hole 58-442. 93 records from Amphibians and Reptiles in Selected Sites in Palawan Province, the Philippines. 2 records from Dysaphis (Dysaphis) kadyrovi sp. nov. ? a new aphid species (Hemiptera: Aphididae) from Tajikistan. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 102 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Gro? Klein. 153 records from Planktic foraminifera abundance of Hole 18-181. 3 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 18540 records from Sistem?tica e historia natural de algunos anfibios y reptiles de M?xico. 1 records from BOTU-Fungi - Herb?rio Irina Delanova Gemtch?jnicov - Cole??o de Fungos. 237 records from Evaluaci?n del ?mbito hogare?o y calidad de h?bitat del borrego cimarr?n (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Bi?sfera El Pinacate y Gran Desierto de Altar. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 343 records from Programme ACT : R?partition Caille des bl?s 2012 - 2016 Coordonn?es GPS Lambert 93. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 17 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 2 records from Microfossil abundance of Hole 21-208. 1848 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 200 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 2041 records from marine metagenome Targeted Locus (Loci). 1 records from Occurrence of mammalia relicts at site Ejstrup. 896 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 24493 records from Plan de vertebrados de la Patagonia. 67 records from Planktic foraminifera distribution of sediment core TRI171-27. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 12869 records from Apoyo a las colecciones biol?gicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 274 records from Planktic foraminifera abundance of Hole 22-217. 3 records from Occurrence of mammalia relicts at site Igstadt I. 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 13000 records from LPO_PACA_2017_12_18. 8 records from Nannofossil abundance of Hole 39-353A. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 42 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biol?gicos CIRN-INTA). 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 724 records from Programme ACT : R?partition Faisan commun 2009 - 2013 Coordonn?es GPS Lambert 93. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 6468 records from Computarizaci?n de la Colecci?n de mam?feros del Centro de Investigaciones Biol?gicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 14344 records from Collection Pisces SMF. 2691 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 41553 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 1584 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 14368 records from Estado actual, identificaci?n de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrol?gicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del r?o de La Laja. 51 records from Total foraminifera counts from M35/1_MSN1051. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 ?m fraction. 1863 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 2950 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 324893 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 9 records from On the Neotropical spider genus Tullgrenella Mello-Leit?o, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 38375 records from Botanical Museum, Copenhagen, Mycology Herbarium. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 11305 records from NCSM Mammals Collection. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 770 records from Niv? Bay species list, Zealand, Denmark. 171 records from Fungal Bioblitz in Bia?owie?a Primeval Forest at 18th Congress of European Mycologists. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 91645 records from Colecci?n de Entomolog?a del Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-E). 211863 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 53 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibd? - Choc?, 2019. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 120 records from Naturschutzgebiet Lochbusch-K?nigswiesen. 19 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 6782 records from Odonata de Veracruz. 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 326 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amaz?nia (INPA). 441 records from L?nea base del medio bi?tico en los bosques dentro de la zona propuesta para Acuerdos de Conservaci?n Voluntaria en la microcuenca de la Quebrada Aguazula - Rinc?n del Soldado_Yopal. 7653 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10295 records from Donn?es naturalistes d'Olivier GARGOMINY saisies sous cardObs. 16506 records from Database for alien invasive plants occurrences in Germany. 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 1335 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 74 records from Birdrace_G?tkes_Schergen-Helgoland. 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 1244 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 98 records from Microfossil abundance of Hole 50-416A. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 2 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 11 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 47 records from Planktic foraminifera counts of sediment core V26-124. 168 records from Caracterrizaci?n flor?stica del humedal La Abuelita, Municipio de Guapi-Cauca, 2018. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 36 records from Selz (Ingelheim am Rhein). 1027 records from Programme ACT : R?partition Merle noir 1996 - 2000 Coordonn?es GPS Lambert 93. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 378 records from Tsetse flies of East Africa update. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 407 records from Strathclyde badger sett surveys 1996-2000. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapaj?s basin, Brazil. 3673 records from Spider (NSMK-SP). 4175 records from OUPR - Herb?rio "Professor Jos? Badini". 10 records from Nannofossil abundance of Hole 58-442B. 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotograf?as a?reas en el parque Chingaza. 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 12399 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San crist?bal). 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 92 records from Nottekanal, Klasse 7 - 10. 574 records from Percentages of planktonic foraminifera species in sediment core V30-40. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 4733 records from Inventaire des Mollusques Sphaeriidae de France. 3919 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geogr?fico y el nicho ecol?gico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 6927 records from Estudios bi?ticos (Plantas, Fauna Ed?fica, Anfibios y Aves) en los Complejos de p?ramos las Hermosas y Chil?-Barrag?n.. 3408 records from Colecci?n de Mam?feros del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 391 records from Vegetaci?n de sistemas c?rsticos en el municipio de El Pe??n, Santander - Proyecto Colombia BIO. 244 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 72142 records from The Environmental Sample Collection of Spiders at the Staatliches Museum f?r Naturkunde Karlsruhe. 133 records from Pollen profile II/B at Krumbach, Germany. 16730 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composici?n flor?stica y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimar?es & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 92 records from Planktic foraminifera abundance of Hole 22-212. 2 records from Nannofossil abundance of Hole 4-26A. 45 records from Universit? P?dagogique Nationale de Kinshasa (UPN) - Le b?tail dans la R?publique D?mocratique du Congo (bases de donn?es des animaux ?lev?s pour consommation)- Projet CABIN. 173 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colecci?n de Peces Dulceacu?colas of Instituto de Investigaci?n de Recursos Biol?gicos Alexander von Humboldt (IAvH-P), Colombia. 60 records from Wichita State University Collection. 86 records from Donn?es naturalistes de Pierre-Alexis RAULT. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 327 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 253 records from NZCS Upper Tapanahony Expedition 1991. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 22 records from Tanzanian Vertebrate Collection. 3 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 3 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 1 records from New record of the genus Baetiella U?no, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 58 records from Donn?es du/de la naturaliste Williamson Thomas provenant de la base de donn?e du SINP ?le-de-France CETTIA. 20 records from Planktic foraminifera abundance of Hole 19-185. 4 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 6 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 1361 records from C?digos de barras de la vida en peces y zooplancton de M?xico. 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 10 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 5 records from Loricifera - SMF. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 32 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 833 records from Plant species from the sacred and community forests of Mono departement. 479121 records from KTP Ring Data. 583 records from Colecci?n Ornitol?gica-Museo de Historia Natural Unillanos. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 2252 records from Synth?se de la R?partition des populations de cerf ?laphe en 2000 (r?seau Ongul?s sauvages ONCFS-FNC-FDC). 462 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 1478 records from Programme FLASH : R?partition Pluvier dor? 2012 - 2016 Coordonn?es GPS Lambert 93. 41 records from Morphologische Daten von Natrix. 3 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 46 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 103 records from Collection botanique Lamy de la Chapelle E. (BOUM). 12457 records from Brown University Herbarium. 89 records from Donn?es du/de la naturaliste Le baron Gaetan provenant de la base de donn?e du SINP ?le-de-France CETTIA. 875 records from Caracterizaci?n biol?gica de la ventana de biodiversidad Montes de Mar?a, Municipio de Colos?, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 19317 records from Inventaire de la flore des Pyr?n?es-Atlantiques 2017 - Littoral. 71 records from Occurrence of mammalia relicts at site Spitzbubenh?hle. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 23 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 17 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 1 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 712 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 24 records from RNF - Donn?es de la R?serve Naturelle du Marais de Lavours. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 1477 records from Inventaire des esp?ces v?g?tales productives dans les Syst?mes Agro-forestiers aux alentours de la For?t class?e de Ziama en Guin?e Foresti?re (BID-AF2015-0066-REG). 90 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 588 records from artsprosjektet_51-14_ophiostomatoid_fungi. 201 records from Biodiversity of springs and rock seepages 2003. 10776 records from CEFS_16S_ITS. 11 records from Inventaire et regroupement de donn?es Natura 2000. 1198 records from Actualizaci?n de la base de datos de crust?ceos y registro de datos de peces del pac?fico mexicano de la Colecci?n Biol?gica de la Secretar?a de Marina (Peces). 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 8 records from Revision of the endemic Philippine Poeciloterpa St?l (Hemiptera: Cercopidae) with description of four new species. 140 records from Planktic foraminifera abundance of Hole 37-332. 521 records from Schanzenanlage Bergham. 74 records from Reptiles de la expedici?n al R?o Apaporis - Proyecto Colombia BIO. 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 833 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 72 records from Total foraminifera counts of multinet POS231/3_MSN1332. 961 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 395 records from Nannofossil abundance of Hole 37-334. 59 records from Schulgel?nde SGD/Viersen. 1533 records from Donn?es du/de la naturaliste ARNABOLDI Fr?d?ric provenant de la base de donn?e du SINP ?le-de-France CETTIA. 63 records from Planktic foraminifera abundance of Hole 73-520. 17 records from Nachtinsekten am Muldenufer. 194 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 19 records from Colecci?n de muestras biol?gicas del Centro Oceanogr?fico de Canarias. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 50 records from Liogenys Gu?rin-M?neville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae) from the southern South American Transition Zone and boundaries: taxonomic overview with four new species. 8 records from Neofidia Strother, a new name for Fidia Baly, 1863 and redescription of Fidia kanaraensis (Jacoby, 1895) with a new host record and notes on natural history (Coleoptera, Chrysomelidae, Eumolpinae). 5883 records from MfN - Fossil vertebrates IV. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 352 records from Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 11469 records from Cat?logo de insectos de la colecci?n del Centro de Entomolog?a. 1607 records from MEXU/Flora de Oaxaca. 36849 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 5 records from Luciobarbus lanigarensis and L. numidiensis, two new species of barbels from the Mediterranean Sea basin in North Africa (Teostei: Cyprinidae). 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 76 records from Records at sea of juveniles southern elephant seals (Mirounga leonina) from Pen?nsula Vald?s, Argentina. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 1 records from Emeia gen. nov., a new genus of Luciolinae fireflies from China (Coleoptera: Lampyridae) with an unusual trilobite-like larva, and a redescription of the genus Curtos Motschulsky. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 207 records from Nannofossil abundance of Hole 66-488. 24 records from Catalogue of Coleoptera type specimens housed in the collection of the Museu de Ci?ncias Naturais, Funda??o Zoobot?nica do Rio Grande do Sul, Brazil. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crust?ceos, equinodermos y peces) del Santuario Islas e Islotes de Bah?a Chamela, Jalisco, M?xico. 6 records from Revision of the genus Coeliccia Kirby in Borneo part II: Two new species from the membranipes- group, with a redescription of C. macrostigma Laidlaw (Odonata: Zygoptera: Platycnemididae). 435 records from Bulletin de la Soci?t? Linn?enne de Bordeaux, Tome 143 (N.S) n? 36 (2), 2008 - Donn?es faune. 3 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 102 records from DAYO: Invasive Alien Reptiles in the Philippines. 16 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 3097 records from Synth?se 10x10km de la faune sauvage de la Directive Habitats-Faune-Flore recens?e par l'association Vienne Nature de 2013 ? 2017. 2933 records from Donn?es naturalistes d'Alain BERLY. 27676 records from Insect Collection from the Museu Nacional de Hist?ria Natural e da Ci?ncia, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 235 records from New state records for Coniopterygidae (Neuroptera) with an updated list of species in North America north of Mexico. 26 records from Chronicle of Nature - Phenology of Mammals of Kondinskie Lakes National Park named after L. F. Stashkevich. 11 records from Catalogue of Notomastus M. Sars, 1851 (Annelida, Capitellidae) and the description of a new species from the Gulf of California. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 2501 records from Aves del Distrito de P?ramos en los departamentos de Nari?o-Putumayo. 61 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 250 records from Inventaire et regroupement de donn?es Natura 2000. 10 records from Species of Horismenus Walker (Hymenoptera: Eulophidae) associated with bruchid beetles (Coleoptera: Chrysomelidae: Bruchinae), including five new species. 12719 records from Donn?es bibliographiques et opportunistes Mammif?res du Nord Pas-de-Calais issues du SIRF. 637617 records from Donn?es de la flore d?Alsace (SBA). 3968 records from Antarctic Jellyfish. 18 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 12 records from Occurrence of mammalia relicts at site Luttenberg. 75 records from Donn?es naturalistes d'Audrey SAVOURE-SOUBELET. 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkham? 1937 (Orthoptera: Tetrigidae: Tetriginae). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 594658 records from National Trust Species Records. 6756 records from Diversit? floristique des esp?ces menac?es prioritaires du B?nin (Afrique de l'Ouest).. 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 253 records from Pukkellaks i Norge 2017. 696 records from the diversity of anammox bacteria in the subterranean estuary. 20383 records from Apoyo a las colecciones biol?gicas de la Facultad de Ciencias de la UNAM: Fase 1 (Collembola). 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Donn?es Mammif?res Midi-Pyr?n?es enregistr?es dans BazNat - Lot 1. 74 records from Etude d'?tat initial de la biodiversit? dans le cadre des EIES sur les plateaux situ?s dans la zone sud de la concession mini?re de Guinea Alumina Corporation(GAC) dans la region de Bok? (CESP2016-022). 384 records from Nannofossil abundance of Hole 17-167. 35 records from Universit? P?dagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 176 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 80 records from Donn?es naturalistes d'Emmanuel ICARDO. 7265 records from NHM, Heteroptera. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 1 records from Revision of the subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox (Hymenoptera: Pompilidae: Pepsinae). 110511 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 423 records from Programme ACT : R?partition Caille des bl?s 2008 - 2012 Coordonn?es GPS Lambert 93. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1 records from A new shrimp species of the genus Lebbeus White, 1847 (Crustacea: Deacpoda: Caridea: Thoridae) from a deep-sea cold seep site off southwestern Taiwan. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 5221 records from Acoustic monitoring data of anuran species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 1555478 records from Flore Franco-Belge. 16547 records from EAC - Herb?rio Prisco Bezerra. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1531 records from Leif Richardson Vermont Bee Specimens. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur ? ventre jaune - ?tude de r?partition. 9116 records from Collection Crustacea - ZMB. 740 records from Estudio herpetofaun?stico de la Sierra Mazateca, Oaxaca, M?xico. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 30 records from Nannofossil abundance of Hole 9-82. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 1939 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 ?m fraction. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 55 records from Occurrence of mammalia relicts at site Rusenschlo?. 2095 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 1211 records from Tejidos de ejemplares colectados en el P?ramo de Chingaza - Proyecto Colombia Bio. 96 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 11 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 162 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 615 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 15251 records from Universidad Aut?noma de Madrid, Madrid; Lepid?pteros. 40738 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 1 records from Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate. 13 records from Lane 6 Analysis. 3939 records from Census of plant species in Pahou forest reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 6578 records from Ibaraki Nature Museum, Fungi collection. 183 records from Relative abundance of ostracods in sediment core Sv09. 911 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 781 records from Ecological study of the plankton in the port of Ostend in 1965. 192 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 93324 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 49 records from Atelier Malacologie continentale, 14-15septembre, La Fl?che (Sarthe). CEN Pays de la Loire. 14 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 20442 records from Trondheim urban biodyversity survey. 94 records from Donn?es du/de la naturaliste LUSTRAT Philippe provenant de la base de donn?e du SINP ?le-de-France CETTIA. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 142 records from Size of planktic foraminifera at CTD station PS55/083-1. 303 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 34525 records from R. L. McGregor Herbarium Lichen Collection. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 12 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 200 records from Cole??o de Bryozoa do Museu Nacional - UFRJ. 557 records from Corn bunting breeding distribution in Scotland. 919 records from Cole??o Zool?gica de Refer?ncia da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 336 records from KARSTLANDSCHAFT S?DHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am R?seberg). 71 records from Foraminifera species abundances from tow TT007_7-MOC13. 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 40011 records from Banded Iron Formation and Greenstone survey data. 38 records from Microzooplankton abundance and biomass at station TT045_19-3. 4 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 131 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 51 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 30 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 1894 records from Fungi Collection. 2 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 87 records from Donn?es esp?ces - Expertise IPE 70. 1028 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 20 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 30954 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 152 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 84312 records from NE AVH data. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 48 records from Schulgel?nde (Wetter). 282 records from Deponie Klausdorf. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 55 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 22800 records from Floristische Kartierung ?sterreichs - Mapping the Flora of Austria. 1986 records from Observations de Col?opt?res saproxyliques de Fr?d?ric LACOSTE. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 29 records from Benthic foraminifera abundance of Hole 42-379A. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 2 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 1489 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality ? Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 1462 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 2548 records from BioGIS - Reptiles - HUJ collections. 13 records from Analyses of the recent components of sediment core PS1222-1. 901635 records from Flora Atlas N.T.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 3 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, ?CT scans, drawings and DNA sequence data). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 129 records from Donn?es du/de la naturaliste jourdan christian provenant de la base de donn?e du SINP ?le-de-France CETTIA. 147 records from Revision of the spider genus Hoplopholcus Kulczy?ski (Araneae, Pholcidae). 754 records from Programme ACT : R?partition Grive draine 2001 - 2005 Coordonn?es GPS Lambert 93. 1856 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 186 records from Interstitial and parasitic Platyhelminthes from the coast of the Seychelles in 1992 and 1993. 10 records from Ostracoda abundance of Hole 32-306. 990 records from Colecci?n base (BGVPA) del Banco de germoplasma del Jard?n Bot?nico Atl?ntico de Gij?n. 244 records from Nannofossil abundance of Hole 29-281. 3856 records from Proyecto interno ejecutado por la CONABIO: Sistema de informaci?n sobre Bosque Mes?filo de Monta?a de M?xico para apoyo en programas de restauraci?n (Fase 1). 580 records from Rare plants database extract from Scottish Natural Heritage. 13 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 314 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 68377 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27220 records from Formidabel; Belgian Ants Database. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 126 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 113 records from Total foraminifera counts of multinet M26/1_MSN844. 7 records from Taiwanese deep-water chitons (Mollusca: Polyplacophora) and survey of chiton fauna of Taiwan. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 3125 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 5673 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 583 records from Donn?es du naturaliste Christian Desmier. 9 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paran?, Brazil. 836 records from Odoanta of Akwa Ibom State University, Nigeria. 1134 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 192 records from Diversidad y conservaci?n del germoplasma de henequ?n Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 11884 records from Donn?es naturalistes de Franck NOEL. 2 records from A new Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the northern Western Ghats, Maharashtra, India. 364 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 853 records from Planktic foraminifera abundance of Hole 80-549A. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 294 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE275. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 30 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2000. 6 records from A new forest dwelling button spider from South Africa (Araneae, Theridiidae, Latrodectus). 361 records from Nannofossil abundance of Hole 66-490. 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 768 records from (Figure 8c) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-536. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-101BX. 130 records from Synth?se de la R?partition des populations de bouquetin des alpes en 2005 (r?seau Ongul?s sauvages ONCFS-FNC-FDC). 111 records from Benthic foraminifera abundance of Hole 34-320. 53 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 52646 records from Herbarium Senckenbergianum (FR). 48879 records from Invertebrate Zoology Division, Yale Peabody Museum. 276 records from DREAL Auvergne - Reptiles - 2015. 449 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 119 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 916 records from Evaluaci?n de la efectividad de las m?tricas derivadas de los invertebrados acu?ticos para establecer la integridad ecol?gica de r?os de p?ramo: caso de estudio del Parque Chingaza. 238 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 40914 records from Managing West African Bees in the implementation of a first reference collection: Bees caught in three areas of Burkina Faso. 483 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V23-82. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 493 records from Programme ACT : R?partition Etourneau sansonnet 2007 - 2011 Coordonn?es GPS Lambert 93. 820 records from Nannofossil abundance of Hole 82-558A. 1257 records from Sea trout entering the rivers Adour and Nivelle in south-west France at the start of the 21st century. 446 records from Programme ACT : R?partition Etourneau sansonnet 2006 - 2010 Coordonn?es GPS Lambert 93. 3327 records from BioGIS - Mammals - SPNI. 1 records from The advertisement call of Leptobrachella liui Fei and Ye, 1990 (Anura: Megophryidae). 576 records from Ecological inventory of Borassus aethiopum (Mart.) populations in the Pendjari Biosphere Reserve, Benin. Data mobilized in the framework of JRS Benin project. 1054 records from Mound building termites contribute to savanna vegetation heterogeneity- woody plants, forbs and graminoids. 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Direcci?n General de Medio Natural y Pol?tica Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 146 records from (Table 2) Expected and observed beluga (Delphinapterus leucas) sightings according to habitat characteristics. 13 records from Diatom abundance of Hole 60-460. 14 records from Registros de tortuga de r?o (Podocnemis lewyana) en el marco del Proyecto: Gen?mica de la conservaci?n para la tortuga de r?o. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 ?m fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 ?m. 16885 records from donn?es aran?ologiques de CORNIC Jean-Fran?ois. 742 records from Programme ACT : R?partition Alouette des champs 2000 - 2004 Coordonn?es GPS Lambert 93. 54 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 2929 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 38 records from Phytoplankton counted on two fractions of surface sediment samples from stations B-5 to B-47. 33 records from Planktic foraminifera abundance of Hole 14-144. 2572 records from seawater metagenome Metagenome. 364 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 746 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 4372 records from Heliconiine Butterfly Collection Records from University of Cambridge. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 943 records from Programme ACT : R?partition Tourterelle turque 2012 - 2016 Coordonn?es GPS Lambert 93. 16 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 255 records from Tejidos colectados en el p?ramo de Pisba, Boyac? - Proyecto Boyac? BIO. 79 records from Birdrace-Bielefinken-Bielefeld. 4054 records from Fish specimens of Toyama Science Museum. 121 records from Range table from ostracoda in ODP Hole 143-866B. 6004 records from Colecci?n Limnol?gica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-L?beck. 3529 records from A dataset from bottom trawl survey around Taiwan. 11661 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 140765 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 8 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 1 records from A mid-Cretaceous female scale insect (Hemiptera: Sternorrhyncha: Coccomorpha) in Burmese amber. 191 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 5 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 14 records from (Table 4b) Biomass of Emiliania huxleyi and its role in total biomass of phytoplankton along the section from the Pribilofs Islands to the Nunivak Island on 24-25 August 2001. 12 records from Lepidoptera specimen database of Japan. 294817 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 37 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 356 records from Planktic foraminifera abundance of Hole 68-503B. 130 records from BIRDRACE - The famous Grouse feat. The James. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 6419 records from VIES herbarium - Universidade Federal do Esp?rito Santo - Herb?rio Virtual REFLORA. 294 records from Aves de la expedici?n en el p?ramo El Valle, Boyac? - Proyecto Boyac? BIO. 22 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 ?m. 536 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 5 records from Three?new country records from the genus?Limnephilus?Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 6 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper R?o Magdalena, Colombia. 52 records from Occurrence of mammalia relicts at site Goyet Cave 3. 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Do?a Josefa, Municipio del Atrato - Choc?, 2019. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 1270 records from Donn?es du/de la naturaliste Lantz Andr? provenant de la base de donn?e du SINP ?le-de-France CETTIA. 70 records from Gew?sser des Wartbergparks Stuttgart (bei der ?kostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 62 records from Donn?es naturalistes de BONCHE J?r?me. 304 records from Base de datos de fauna batial, abisopel?gica y abisal del Golfo de M?xico. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 ?m fraction. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 79758 records from natagora-earlybirds. 8985 records from Universidad de Murcia, Dpto. Biolog?a Vegetal (Bot?nica), Murcia: MUB-MUSCI. 18 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 29 records from Reptiles Specimens of Akita Prefectural Museum. 338 records from UWIZM Snakes. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 182 records from Tejidos colectados en el piedemonte llanero, Boyac? - Proyecto Boyac? BIO. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 75152 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 2369 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 111 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 13 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-104BX. 119365 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 176 records from Planktic foraminifera abundance of Hole 94-610B. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 2082 records from Registros biol?gicos de flora para el desarrollo de acciones de evaluaci?n, seguimiento y monitoreo en los elementos priorizados de la estructura ecol?gica principal del distrito capital. Bogot? D.C.. 113 records from Arizona State University Lois B. O'Brien Collection. 52 records from Occurrence of mammalia relicts at site Zigeunerfels. 2 records from Description of lithologic section units of IODP Hole 325-M0052C. 47 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 7178 records from Ravensthorpe Range survey data. 5 records from Scorpaena regina, a new scorpionfish (Teleostei: Scorpaenidae) from the east coast of Queensland, Australia. 56 records from Ictiofauna balseana y helmintos par?sitos asociados. 5 records from Schulinnenh?fe (Gelsenkirchen). 395 records from (Table 2) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Pacific Ocean side). 12 records from Analyses of the recent components in the sand fraction of sediment core PS1012-1. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 31 records from Nanoplankton abundance at station GeoB2012-5. 841 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 7484 records from Yoann_BLANCHON_2017_12_18. 1 records from Notes on the genus Gargela (Lepidoptera: Crambidae) ? with descriptions of two new species from China. 1012 records from Programme ACT : R?partition Merle noir 2000 - 2004. 3 records from MSB Mammal Observations (Arctos). 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 10 records from Donn?es naturalistes de Sophie COHEN. 53 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 2 records from The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Malaysia, with the description of four new species. 20068 records from Wikiplantbase #Sicilia. 123 records from NEON Biorepository Zooplankton Collection (Unsorted Bulk Sample). 1879 records from Database of Australasian Vertebrate Occurrences. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 498 records from Bekkelag basin, Inner Oslofjord. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 2023 records from Composici?n flor?stica y estructura vegetal de una parcela permanente en un relicto de bosque seco tropical en el Caribe colombiano. 748 records from Phenological Center - Birds (Laplandskiy). 609 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 551 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 48 records from Benthic foraminifera abundance of Hole 42-380. 57 records from Inventaire faune flore de l'?tang d'Abbecourt ? Orgeval. 1010731 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 60 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 58 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 29105 records from Marine Biological Sample Database, JAMSTEC. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 362 records from Otter (Lutra lutra), Outer Hebrides. 874 records from The Living Murray Fish data. 4428 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 25974 records from Long-term Bird Census in Cigu 2004-2017. 7 records from Contribution to the AIrotropical ?chneumoninae (Hymenoptera, ?chneumonidae) Irom Gabon and Sierra Leone, with descriptions oI Iive new species and two new subspecies. 4 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 240 records from BARTH-Environnement_2017_12_18. 1084 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 493 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 156 records from Total foraminifera counts of multinet M21/2_MSN658. 34 records from Microzooplankton abundance and biomass at station TT043_11-1. 1956 records from Colecci?n de Entomolog?a - Hymenoptera - Chalcidoidea. 1377 records from Ghent university - Zoology Museum - Nematod Collection. 79 records from Swedish Malaise Trap Project (SMTP) - Syrphidae. 101 records from BIRDRACE Enger am Spektiv. 32 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 125 records from Total foraminifera counts from multinet M32/3_MSN956. 6164 records from Donn?es naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 10 records from Donn?es naturalistes de CLERGET sylvie. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 7 records from Stadtrandlandschaft Apolda-Nord. 12 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 40 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 2 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 7 records from Notes on slender species of the long-jawed spider genus Tetragnatha (Araneae Tetragnathidae) with description of three new species. 3230 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 322193 records from Florida Keys Reef Visual Census 2010. 153 records from annex1. 123 records from Total foraminifera counts of multinet POS247/2_MSN1377. 28 records from Dinoflagellate abundance of Hole 28-270. 693 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils at DSDP Hole 93-603B. 2 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 62 records from Rare vascular plant species in North-West of Kostroma region, Russia. 2 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 6 records from Four new species of the genus Pseudosubhimalus (Hemiptera: Cicadellidae) from the Indian subcontinent. 332 records from Swedish Malaise Trap Project (SMTP) - Sepsidae. 22 records from Description of lithologic section units of IODP Hole 325-M0054B. 2565 records from AlgaTerra. 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 729 records from MfN - Fossil vertebrates III. 47 records from Abundance and community structure of birds breeding in Kalahari woodland used as rangeland. 165 records from HSU Vertebrate Museum Mammals Collection. 13 records from Nannofossil abundance of Hole 9-80. 10 records from Umbyquyra gen. nov., a new tarantula spider genus from the Neotropical region (Araneae, Mygalomorphae, Theraphosidae), with a description of eight new species. 37445 records from ADDOMEx. 1 records from The InBIO Barcoding Initiative Database: Wesmaelius (Kimninsia) nervosus (Neuroptera, Hemerobiidae): a new species of brown lacewing for the Portuguese fauna. 305 records from Foraminifera abundance of Hole 57-440B. 124 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 245 records from Informatisation des carnets de terrain de Georges Catherine. 98734 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 26441 records from UTEP Insects (Arctos). 1 records from Revision of the Genus Schizoretepora (Bryozoa, Cheilostomatida) from the Atlantic-Mediterranean region. 10 records from Donn?es naturalistes de DURON Cyril. 1339 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 39 records from Inventaire Faune. 31 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 208 records from Registros de ara?as en el marco del proyecto Influencia de la dieta sobre la toxinolog?a y toxicolog?a en ara?as. 1 records from Revision of the genus Carybdea (Cnidaria: Cubozoa: Carybdeidae): clarifying the identity of its type species Carybdea marsupialis. 6 records from Review of the genus Shilovia Makarchenko (Diptera: Chironomidae: Diamesinae Boreoheptagyiini) from the mountains of Central Asia, with morphological description and DNA barcoding of known species. 4 records from Sponges of the family Esperiopsidae (Demospongiae, Poecilosclerida) from Northwest Africa, with the descriptions of four new species. 525 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 183 records from Nannofossil abundance of Hole 67-496. 852 records from Observatoire des Mammif?res marins de l'Archipel Guadeloup?en. Suivi Dauphins Les Saintes. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 841 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 525 records from Flora y fauna asociada al h?bitat del Manat? antillano en la Ci?naga de Paredes, Magdalena Medio Santandereano. 2 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 2 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 361 records from Colecci?n de Crust?ceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 235 records from Pollen and spore abundance of Hole 42-381. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 932 records from CNAN/Araneae. 42 records from Estimated plankton abundance at station PS63/064-6. 28 records from Anfibios y reptiles de la expedici?n en el p?ramo de Bijagual, Boyac? - Proyecto Boyac? BIO. 358 records from Comunidad fitoplanct?nica presente en la Bah?a de Buenaventura 2018. 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 372 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 1084 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 1359 records from GEO Biodiversity Day. 351600 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 3 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 15 records from Inventaire et suivi de la Cistude d?Europe sur le site Natura 2000 ?Zones humides de Moliets, La Prade et Moisans? (FR7200718). 22 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 886 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 102 records from Colecci?n de Zoolog?a Invertebrados - Helmintolog?a. 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 8 records from Lynx 1988 pr?sence R?guli?re Mailles 10km R?seau Loup-Lynx ONCFS. 105 records from Conocimiento integral del tapir (Tapirus bairdii) y el pecari de labios blancos (Tayassu pecari) en M?xico. 79 records from Total foraminifera counts of multinet POS247/2_MSN1384. 25487 records from Fishes of INEP and NFH collections. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 243726 records from Carnet B Lorraine. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 1947 records from Lapwing Recovery Project, South West Scotland, 2006-2009. 176 records from Recursos hidrobiol?gicos de Ca?o Cristales, La Macarena, Meta. 267972 records from Limnic freshwater benthic invertebrates biogeographical mapping/inventory NTNU University Museum. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 23 records from TBW-Schafberg. 111 records from Birdrace-Uhulogen-Lippe. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/045-2. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 4266 records from Observations et collection de Col?opt?res d'Alain Sadorge. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 7010 records from La familia Asclepiadaceae en M?xico. 25 records from Total foraminifera counts of multinet M42/3_MSN1368. 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 4 records from Notes on the spider genus Segestria Latreille, 1804 (Araneae: Segestriidae) in the East Palaearctic with description of three new species. 753 records from Caracterizaci?n biol?gica de la ventana de biodiversidad R?o Guamu?s, corregimiento El Encano, Municipio de Pasto, Nari?o, Colombia. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 19 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 ?m fraction. 373 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Donn?es opportunistes produites par Alexandre RUFFONI dans le cadre de l??laboration d?un guide de d?termination des larves de pl?copt?res. 13 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopaloc?res de France (STERF). 131 records from Unser Schulhof - eine Apotheke. 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 54 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 1 records from Chance, luck and a fortunate finding: a new species of watersnake of the genus Helicops Wagler, 1828 (Serpentes: Xenodontinae), from the Brazilian Pantanal wetlands. 64 records from B herbarium - Botanischer Garten und Botanisches Museum Berlin-Dahlem Herbarium - Herb?rio Virtual REFLORA. 1686 records from Southern Maine Community College Gulf of Maine Invertebrate Data. 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 37 records from Berlin - Treptower Park / Karpfenteich. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 247577 records from Bacterial diversity and community composition in grassland and forest soils of the German Biodiversity Exploratories. 561 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 23 records from Donn?es d'observation d'?crevisses exotiques envahissantes en Nouvelle Aquitaine sur la p?riode 2014 ? 2018. 8165 records from El g?nero Bursera en M?xico. Parte II. 61 records from Alien Species in Poland - Plants. 14003 records from HUFU herbarium - Universidade Federal de Uberl?ndia - Herb?rio Virtual REFLORA. 71 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 323-U1341. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 323 records from Donn?es de VINCENT Alexis (SAPROX). 447 records from PSUZC-Mammal Collection. 161 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 3 records from Two new marine species of Cocconeis (Bacillariophyceae) from the west coast of Sweden. 3 records from The Cephenniini of China. IX. Cephennomicrus Reitter of Yunnan (Coleoptera: Staphylinidae: Scydmaeninae). 3 records from Occurrence of mammalia relicts at site Sesselfelsgrotte. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 56 records from Donn?es de la structure For?ts en Aulnoye provenant de la base de donn?e du SINP ?le-de-France CETTIA. 371 records from GCP_2017_12_18. 361 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 87 records from Gulf of Gdansk. 55 records from Macroinvertebrados bent?nicos de playas de arena (Monte Hermoso-Pehuen C?, Buenos Aires, Argentina). 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 5586 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 119 records from Suivi des leucorrines sur le site du Marais du Plata. 39621 records from ALCB herbarium - Universidade Federal da Bahia - Herb?rio Virtual REFLORA. 127 records from ?ypripedium guttatum Sw. in the Komi republic. 146 records from Abundance of birds in the Lena Delta Region. 31 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 79 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 433 records from Synth?se de la R?partition des populations de chamois en 1988 (r?seau Ongul?s sauvages ONCFS-FNC-FDC). 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 39 records from Planktic foraminifera counts of sediment core V19-21. 69 records from artsprosjektet_48-13_monomyx. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 1188 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 5360 records from Colecci?n Ornitol?gica de la Universidad del Valle. 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 1668 records from The ? red-tailed? Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 188 records from Donn?es de Mammif?res marins. Mission Sanctuaire AGOA de 2012 ? 2014. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 224 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 159 records from Total foraminifera counts from multinet M31/3_MSN915. 41676 records from Tagged Seal Location Data from SOGLOBEC. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 333 records from Donn?es naturalistes de Renaud PUISSAUVE. 839 records from Pollen analysis of sediment profile HAE10 from H?melsee. 1748 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 1709 records from The Gibson spider collection. 56 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 195 records from Truppen?bungsplatz Panzerkaserne B?blingen. 651 records from R?seaux ?cologiqu
Keywords: GBIF; biodiversity; species occurrences